Empowering Sustainable School Innovation Through Islamic Leadership and Islamic Business Ethics - Astri Ayu Purwati; Zulfadli Hamzah; Muhammad Arif; Mazzlida Mat Deli; Duwi Riningsih; Meme Rukmini (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
The growing demand for sustainable innovation in educational institutions underscores the importance of leadership models grounded in ethical and religious values. In the context of Islamic education, leadership is not only expected to drive organizational performance but also to uphold Islamic ethical principles that shape decision-making and innovation practices. This study aims to examine the influence of Islamic Leadership on sustainable school innovation, with Islamic Business Ethics serving as a mediating variable. The research focuses on Islamic private schools in Pekanbaru, Indonesia. The study employs a quantitative research design using a survey method. From a total of 349 Islamic private schools, 100 schools were selected as the research sample using purposive sampling. Data were collected from school leaders and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software to test both direct and indirect relationships among variables. The findings reveal that Islamic Leadership has a significant and positive effect on sustainable school innovation. Furthermore, Islamic Leadership positively influences the implementation of Islamic Business Ethics. The results also confirm that Islamic Business Ethics significantly mediates the relationship between Islamic Leadership and school innovation, indicating that ethical practices strengthen the impact of leadership on innovation outcomes. These findings imply that integrating Islamic ethical values into leadership practices is essential for fostering sustainable innovation in Islamic educational institutions. In practice, school leaders are encouraged to embed Islamic Business Ethics into the organizational culture to enhance innovation and long-term educational sustainability.